Alternatively spliced isoforms of the human constitutive androstane receptor - Auerbach, Scott S. (Oxford University Press, 2003)
The nuclear receptor CAR (NR1I3) regulates transcription of genes encoding xenobiotic- and steroid-metabolizing enzymes. Regulatory processes that are mediated by CAR are modulated by a structurally diverse array of chemicals including common pharmaceutical and environmental agents. Here we describe four in-frame splice variants of the human CAR receptor gene. The variant mRNA splice transcripts were expressed in all human livers evaluated. Molecular modeling of the splice variant proteins predicts that the structural effects are localized within the receptor’s ligand-binding domain. Assays to assess function indicate that the variant proteins, when compared with the reference protein isoform, exhibit compromised activities with respect to DNA binding, transcriptional activation and coactivator recruitment.